Analysis of Chlorine Inventory Using the Economic Order Quantity (EOQ) Method (Case Study of PT. Toya Indo Manunggal) - Putri, Nirmala; Momon, Ade (JTI: Jurnal Teknik Industri, 2024)
The purpose of this study was to determine the frequency of ordering chlorine for one year at PT. Toya Indo Manunggal using the Economic Order Quantity (EOQ) method, to determine the cost of chlorine supplies of PT. Toya Indo Manunggal with the Economic Order Quantity (EOQ) method, as well as to analyze the results of the application of the Economic Order Quantity (EOQ) method. The research method used in this study is the economic order quantity (EOQ) model. Data collection techniques are used to collect data according to research procedures so that the required data is obtained. The data used is secondary data in the form of literature studies, namely conducting literature research by reading and researching materials or theories related to chlorine supplies, and Economic Order Quantity (EOQ). The results showed that the frequency of ordering chlorine for one year at PT. Toya Indo Manunggal uses the Economic Order Quantity (EOQ) method of 112 chlorine cylinders per order with a total of 13 orders in one year, the distance between times reaches 20 days per order, and the company must provide security storage or Safety Stock of 142 chlorine cylinders with goods reorder activities when the inventory of the goods is 178 pcs. From data analysis, the total cost of inventory using the EOQ method is Rp. 940,802,000, while the total cost of inventory with orders above and below EOQ is Rp. 1,034,137,777 and Rp. 985,012,631, respectively. Every order for goods above or below the EOQ order will affect the cost of inventory, where the cost of inventory that occurs is greater than the cost of EOQ inventory. With the Economic Order Quantity (EOQ) method, companies can find out how many orders are economical for each inventory item and find out the frequency of orders during a period and when orders are made again, so that the demand for goods can be fulfilled optimally.